Pengaruh Kualitas Audit terhadap Manajemen Laba Riil dengan Corporate Governance sebagai Moderasi - Meinie Susanty (Jurnal Bisnis dan Akuntansi, 2022)
The purpose of this study is analyze of effect audit quality on real earning management with corporate governance/CG as moderating. Previous study have found that high audit quality bring implication for manager to do real earning management because there is limitation of overstated asset in balance sheet for doing discretionary accrual earning management. Measurement of audit quality use multidimension aspect include competence and independent aspect of auditor with analyze of effect of audit quality on real earning management with CG as moderating on public listed company in Indonesia. Indicator of CG use ASEAN Corporate Score Card. Finding found that high audit quality with multidimension measurement Audit Quality Metric Score (AQMS) increase real earning management in production cost abnormally and discretionary accrual, but not with operating cash flow abnormally at individual level and at aggregate level in real earning management group from operating cash flow abnormally, production cost and discretionary accrual. Good corporate governance (GCG) found could moderate cash flow operating abnormally and production cost in real earning management at individual level. Meanwhile GCG could not moderate real earning management on discretionary accrual at individual level and at aggregate level on operating cash flow abnormally, production cost, and discretionary accrual. This study have implication to audit quality research that use multidimension measurement include competency and independent of auditor with AQMS and real earning management real with CG ASEAN Corporate Score Card as moderating.